The beginner's guide to photographing birds : essential techniques for hobbyists and bird lovers - Rössner, Rosl (Rocky Nook, 2022)
Whether you’re a dedicated and serious birder, a hobbyist bird watcher, or simply a lover of nature, getting great photos of birds is at the top of the list for bird lovers of all kinds. In this book, professional photographer Rosl Rössner teaches you all of her techniques, tips, and tricks for capturing fantastic bird photographs. Starting with the gear you’ll need, Rössner discusses cameras, tripods, lenses, and more. She then moves on to finding the birds you want to photograph. While this includes locations out in the wild, she also covers zoos, parks, sanctuaries, and other easily accessible spots—which are especially great for beginning bird photographers. Rössner then thoroughly covers the camera and shooting techniques you need to know, including key lessons on exposure, composition, focus, and sharpness. Regardless of the quality of the light (front light, side light, etc.) or the season you’re shooting in (rain, snow, fog), Rössner’s got you covered. In the final part of the book, Rössner takes you behind the scenes of 25 unique bird photographs, telling you how the image came about, plus any specific tips and tricks that were used to create the image. Featuring birds from around the world, The Beginner's Guide to Photographing Birds is a beautiful, helpful, and accessible guide for anyone getting started in bird photography.